Keanekaragaman, Keseragaman, Dan Dominasi Bivalvia Di Muara Sungai Porong Sebagai Area Buangan Lumpur Lapindo - Insafitri, Insafitri (Rekayasa, 2009)
Porong river is area for dumping of Lapindo mud that have heaavy metal exit thresshold value such as Cd 10,45 ppm, Cr 105,44 ppm, As 0,99 ppm, dan Hg 1,96 ppm. This area estimated influence to structure communi of bivalvia as bioindikator organism. Objectives of this study is estimate stucture comunity of bivalvia in the dumping area of Lapindo mud. Study observe 3 locations and and analyze the abundance, index biodiversity, index uniformity, index aominition. Result of this study snows that no bivalvia found in the dUmping area of Lapindo mud and this area has low biodiversity, uniformity of population is very low, and no species dominate this area. Conclusion of this stuay this area categorized as not good condition.Key words: structure comunity, bivalvia